ANALYSIS OF SERVICE QUALITY BASED ON USER SATISFACTION OF THE ANTERAJA APPLICATION USING THE SERVQUAL METHOD - Li Sensia Rahmawati; Dodo Zaenal Abidin; Errissya Rasywir (International Conference on Business Management and Accounting, 2022)
AnterAja is a company engaged in the delivery of goods, services and logistics based on information technology, headquartered in DKI Jakarta, Indonesia. In this study, an analysis of service quality was carried out which could conclude the public's assessment of AnterAja's expedition. This research was conducted with the aim of knowing whether the quality of service at AnterAja is acceptable or not by users. AnterAja service success measurement is determined by the level of user satisfaction using the SERVQUAL (Service Quality) method. The research data was processed using SPSS 25 software. The significant standard used in the study was 5% (0.05). From the research results show that of the five independent variables, only two variables are accepted significantly, which means that there is an influence, namely Reliability and Responsiveness. While the three variables, namely Tangibles, Assurance, and Empathy, have no significant effect on user satisfaction.